Rumanian Folk Music - Bartok, Bela. author. aut Link
XLII, 604 p.
Keywords: n the first volume of Rumanian Folk Music (Instrumental Melodies) I portions of Bela Bart6k's subsequently-discarded preface, concern ing the fate of his folklore publications, are presented in explanation of the editorial processes necessary for achieving the publication. 1 By way of introduction to this revised edition of a previous, although in complete, published version of the Rumanian Carols and Christmas Songs (Colinde), we refer again to the author's suppressed lines which pertain to this volume: The second publication by the same publisher was to include my collection of Rumanian Colindas (Winter-solstice songs). Their extremely interesting texts were supposed to appear in original as well as in English. After several years of delay, the translation to English prose was completed, one part in adequate archaic English, the rest (by someone else) in most unsuitable Kitchen-English. The publisher did not wish to change this, though. Result: I published the book at my own expense; however, only the musical part, because of lack of sufficient funds. The texts are still in manuscript, even today. 2 Our primary aim, therefore, has been to unite the Rumanian poetic texts and translations with the musical part, in one volume, as was the desire of the author.